The Impact of COVID-19 and Homeschooling on Students' Engagement With Physical Activity - Roe, Astrid; Blikstad-Balas, Marte; Dalland, Cecilie Pedersen (Frontiers in Sports and Active Living, 2021)
The COVID-19 pandemic forced an unprecedented global shutdown that closed schools for months. In many nations, schools were closed to students, and teachers directed educational activities remotely via digital devices or homeschooling resources. This article explores how these months of homeschooling have affected the physical activity of Norwegian students in Grades 1–10. All Norwegian students are supposed to have at least 60 minutes of physical activity every day in school. We draw on data from two surveys, one with parents (N = 4,624) and the other with teachers (N = 726), to provide an indication of the daily physical activity students engaged in during the period of homeschooling. AnOne important finding from the teacher survey is that the degree to which schools prioritized physical education among the school subjects reported physical activity varied greatly between schools and teachersbetween schools and teachers in terms of the amount and type of physical activities the students were offered as well as the degree to which schools prioritized physical activity at home.. Key findings from the parent survey were that The reported time spent on physical activity increased with the age of the students, that was often a direct result of parents’ initiative, and many parents expressed concerns about increased sedentary behavior, and that . Furthermore, the most active students were those who showed the greatest engagement and effort in schoolwork in generalfunctioned well with remote teaching and homeschooling. Our findings raise the questions of whether students were given too much responsibility for their own physical activity during this period and whether teachers should provide their students with more digital workout sessions and instructional videos.